A bibliometric analysis of respiratory mechanics research related to acute respiratory distress syndrome from 1985 to 2023 - Zhou, Yi-Min; Tian, Xiuli; Wang, Yu-Mei; Wang, Shuya; Yang, Yan-Lin; Zhou, Jian-Xin; Zhang, Linlin (Frontiers in Medicine, 2024)
Background Acute respiratory distress syndrome (ARDS) is a severe condition characterized by lung stiffness and compromised gas exchange, often requiring mechanical ventilation for treatment. In addition to its clinical significance, understanding the publication trends and research patterns in respiratory mechanics related to ARDS can provide insights into the evolution of this field from a bibliometric perspective, aiding in strategic planning and resource allocation for future research endeavors. Objective This study aimed to explore the trends and identify the hotspots in respiratory mechanics research related to ARDS. Methods All relevant studies on respiratory mechanics of ARDS published between 1985 and 2023 were retrieved from the Web of Science Core Collection (WoSCC), and the retrieval strategy was topic search “TS = respiratory mechanics OR lung mechanics AND TS = ARDS OR acute respiratory distress syndrome.” Annual trends, citation patterns, and contributions from countries, institutions, authors, and journals were analyzed using Bibliometrix Biblioshiny. Networks and overlay of authors, institutions, countries, journals, co-citations, and keywords were analyzed and visualized using VOSviewer. Results Our analysis included 1,248 articles published between 1985 and 2023, revealing fluctuations in publication output over time. The United States emerged as the leading contributor, with Critical Care Medicine being the most prominent journal. Key research themes included mechanical ventilation, acute lung injury, and protective ventilation strategies. International collaboration was evident, facilitating knowledge exchange and interdisciplinary cooperation. Conclusion Our study sheds light on the evolving landscape of respiratory mechanics research in ARDS. International collaboration is pivotal in advancing the field, while researchers increasingly focus on personalized approaches to address the complexities of ARDS respiratory mechanics.